Utilization of sunflower (Helianthus annuus) heads as roughage source in complete diets - MOHAN, A MADAN; RADDY, G V N; REDDY, M R (The Indian Journal of Animal Sciences, 2013)
Two complete diets containing (i) 40% ground sunflower heads and (ii) 20% ground flower heads + 20% lucerne hay, were compared with a cpnventional diet containing concentrate mixture and chopped sorghum straw fed separately by feeding to 3 permanently fistulated crossbred bulls in digestion and metabolism experiments using 3 x 3 latin square. Organic matter, NFE (P<0.05), CP and lignin (P<0.01) digestibilities were significantly higher on complete diet 2. Complete diet I recorded higher (P<0.01) CP and lignin digestibilities compared to conventional diet. DCP content was significantly (P<0.01) higher on complete diets compared to conventional diet. All the experimental animals on all the diets met DCP and TDN requirements. The concentration of all N fractions and TVF A were significantly (P<0.01) higher on complete diet 2 and lower on conventional diet. All the N fractions peaked at 2 hr post feeding and declined thereafter. pH values were lowest at 2 hr post feeding while TVFA concentrations peaked at 4 hr post feeding.